Remark on classical Crane's solution of viscous flow past a stretching plate. (February 2016) - Aziz, Taha; Mahomed, F.M.
Abstract: An efficient compatibility criterion is proposed to solve the nonlinear boundary problem arising in the study of the classical problem of viscous fluid flow due to a stretching sheet due to Crane (Crane, 1970). The compatibility and generalized group analysis make it simple to obtain the exact solution of the classical boundary layer problem.